Characterisation of australian MRSA strains ST75- and ST883-MRSA-IV and analysis of their accessory gene regulator locus - Monecke, S.; Kanig, H.; Rudolph, W.; Müller, E.; Coombs, Geoffrey; Hotzel, H.; Slickers, P.; Ehricht, R. (Public Library of Science, 2010)
Background: Community-acquired methicillin-resistant Staphylococcus aureus have become a major problem in Australia. These strains have now been isolated throughout Australia including remote Indigenous communities that have had minimal exposure to healthcare facilities. Some of these strains, belonging to sequence types ST75 and ST883, have previously been reported to harbour highly divergent alleles of the housekeeping genes used in multilocus sequence typing. Methodology/Principal Findings: ST75-MRSA-IV and ST883-MRSA-IV isolates were characterised in detail. Morphological features as well as 16S sequences were identical to other S. aureus strains. Although a partial rnpB gene sequence was not identical to previously known S. aureus sequences, it was found to be more closely related to S. aureus than to other staphylococci. Isolates also were screened using diagnostic DNA microarrays. These isolates yielded hybridisation results atypical for S. aureus. Primer directed amplification assays failed to detect species markers (femA, katA, sbi, spa). However, arbitrarily primed amplification indicated the presence of unknown alleles of these genes. Isolates could not be assigned to capsule types 1, 5 or 8. The allelic group of the accessory gene regulator (agr) locus was not determinable. Sequencing of a region of agrB, agrC and agrD (approximately 2,100 bp) revealed a divergent sequence. However, this sequence is more related to S. aureus agr alleles I and IV than to agr sequences from other Staphylococcus species. The predicted autoinducing peptide (AIP) sequence of ST75 was identical to that of agr group I, while the predicted AIP sequence of ST883 was identical to agr group IV. Conclusions/Significance: The genetic properties of ST75/ST883-MRSA may be due to a series of evolutionary events in ancient insulated S. aureus strains including a convergent evolution leading to agr group I- or IV-like AIP sequences and a recent acquisition of SCCmec IV elements. © 2010 Monecke et al.